ARABIC MATERIAL DEVELOPMENT DESIGN BASED ON LOCAL WISDOM MATERIAL IN IAIN PAREPARE - Raodhatul Jannah; Herdah Herdah; Susilawati Susilawati (JURNAL EDUCATION AND DEVELOPMENT, 2024)
Learning Arabic is a compulsory subject for Islamic religious institutions under the Ministry of Religion in the Republic of Indonesia. The State Islamic Institute of Religion (IAIN) Parepare is a State Religious University where every study program other than the Arabic Language Education study program teaches Arabic courses at least 2 credits. So far, learning Arabic seems difficult and not easily understood by students, so that students' interest in learning is also low. To answer these problems, the design of teaching materials based on local wisdom is made to be closer to the situations and conditions of student life. This is also in line with the vision of IAIN Parepare as a Center for Acculturation of Culture and Islam in building a religious, moderate, innovative and superior society. This type of research is development research that seeks to develop Arabic teaching materials that are integrated with local culture. Development of teaching material design using the Addie Model (Analysis-Design-Develop-Implement-Evaluate) teaching material development design. The results show that the design of Arabic teaching materials based on local wisdom is integrated as materials and mufradat that are often used in daily activities and the values of local wisdom of the Bugis community can affect the language learning process and increase students’ willingness to learn.